FAKTOR-FAKTOR YANG DAPAT MEMENGARUHI PROFITABILITAS PERUSAHAAN INDUSTRI BARANG KONSUMSI - Hasugian, Ray Agustinus; Stella, Stella (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
Analyzing and evaluating the influence of current liability, non-current liability, firm size, sales growth, total asset turnover, debt to equity ratio, and current ratio on profitability is the objective of this study. This study used samples of 52 companies in the consumer goods industry that were listed on Indonesia Stock Exchange for 9 years, from 2012 to 2020. The sampling method used was purposive sampling method. By using the purposive sampling method, the samples that met the research criteria were 21 companies. The data obtained were then analyzed using multiple regression. The results of this study indicate that current liability, non-current liability, debt to equity ratio, and current ratio have no effect on profitability. While the others, firm size, sales growth, and total asset turnover have effect on profitability.